Pengaruh Pelatihan, Motivasi Dan Reward Terhadap Disiplin Kerja Pada Karyawan PT XYZ di Kabupaten Bekasi - Khambali, Imam; Setyaningrum, Retno Purwani (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the effect of training, motivation and rewards on the work discipline of PT XYZ employees in Bekasi Regency. This research was conducted atPT XYZ by involving employees as the object of research and a sample size of 57 respondents. Sample calculation using saturated sampling method. The method used is quantitative with a case study design, where data is collected through a questionnaire measured on a Likert scale and analyzed using the SmartPLS 3.0 tool. The results showed that training has a positive effect on employee work discipline, motivation has a positive effect on employee work discipline, and rewards have a positive effect on employee work discipline.